Constitutional Compliance Solution to Law Testing Rulings in the Constitutional Court - Sulistyowati, Tri; Ridho, Ali; Nasef, M Imam (Jambura Law Review, 2021)
One of the current constitutional issues in Indonesia is the non-compliance of the decision to immediately follow up the decision of the Constitutional Court, which is final. This paper aims to analyze forms of non-compliance with the decision of the Constitutional Court and create a model that is expected to be a solution to the problem. This type of research is juridical normative by using secondary data processed by editing and systematization techniques.  The results showed the form of non-compliance of the decision of the Constitutional Court by the addresat of the decision is manifested in 3 (three) forms, namely normative, praxis, and normative and praxis forms. There are three proposed state-regulation solutions, namely judicial deferral by limiting the time of action, re-affirmation of judicial restraint, collaborative action, and collective awareness between state institutions.